مؤسسات الدعم ودورها في التمكين الاقتصادي للمرأة في الجزائر دراسة حالة وكالات ANADE ،ENGEM، CNAC بالشلف : Support institutions and their role in the economic empowerment of women in Algeria case study agencies ANADE, ANGEM,CNAC in chlef - جازية حسيني (Journal of North African Economies, 2025)
This study aimed to highlight the role that support institutions play in promoting the financial and economic empowerment of women in Algeria, specifically the agencies affiliated to the state of Chlef, Which participates in financing projects for various groups, including women. To achieve this goal, the study relied on the analytical descriptive approach, which includes description and analysis of data issued by a group of supporting structures, namely ANADE, ENGEM, CNAC; The results of this study showed that despite Algeria’s efforts such as establishing support agencies to accompany and finance projects in Algeria, it is still lagging behind in many sectors, with the exception of the services sector, which witnessed a significant number of funded women's projects compared to the sectors of maintenance, agriculture, which are the preserve of men, this is also shown by Algeria's rank 140 out of 146 countries in the field of women's empowerment.